Reminiscence of Education in Post-War Years: Sierra Leone as a Case Study - Jackson, Emerson Abraham; Jackson, Hudson Freddie (Educational Challenges, 2023)
The main purposes of this paper are as follows: (I) to provide a historical narrative of Sierra Leone’s educational system, (II) to assess the impact of war on the country’s educational system and pace of development in the current digital age, and finally, (III) to offer some discourses for policy dialogue in embracing the developmental landscape of the country. Methodology. The study is based on a "narrative" approach to exploring the outcomes of the civil war that resulted in the complete disruption of the education system in Sierra Leone. Results. The outcome of the study, which utilizes a narrative methodological approach, has captured pertinent areas of concern regarding the destructive legacy that the civil war brought to the country. Notable among these is the complete collapse of standards in the education system and, even more notably, the emergence of fake educational institutions. The results also draw attention to the positives of free education in creating equality in access to education for all. Conclusions. The study outcome shows that Sierra Leone is making some steady progress in providing an inclusive education for that despite the bad memory that the civil war brought to the entire nation. Moving on, the study outcome noted that progress needs to be made in terms of embracing modern technology to address emerging developments in areas pertaining to Artificial Intelligence (AI) and many more. Also, to resurrect the country to its earlier glory of high educational standards, efforts must be made to raise the profile of those responsible for delivering the curriculum (teachers in particular), while at the same time ensuring high quality of graduates are made to enter through competitive salaries.